Interface-Coupling of NiFe-LDH on Exfoliated Black Phosphorus for the High-Performance Electrocatalytic Oxygen Evolution Reaction - Fan, Jinchen; Qin, Xi; Jiang, Wendan; Lu, Xiaolei; Song, Xueling; Guo, Wenyao; Zhu, Sheng (Frontiers in Chemistry, 2022)
Electrochemical oxygen evolution reaction (OER) always plays an important role in many electrochemical energy storage and conversion systems. Owing to the slow kinetics mainly brought from multiple proton-coupled electron transfer steps, the design and exploit low-cost, highly active, durable OER electrocatalysts is of significant importance. Although the black phosphorus (BP) shows good electrocatalytic OER performance, it still faces the problems of poor intrinsic activity and low stability due to its instability under ambient conditions. Herein, the NiFe LDH was assembled onto the surfaces of exfoliated BP (EBP) nanoflakes to realize the interfacial coupling between them, achieving an effective improvement in electrocatalytic activity and stability. Benefitting from the interfacial P-O bonding, the NiFe LDH@EBP hybrid shows high OER activity with a low overpotential of ~240 mV@10 mA·cm-2 toward OER in alkaline condition, as well as the good stability. Density functional theory (DFT) calculations proved that the interface-coupling of NiFe LDH on BP promotes charge transfer kinetics and balances the adsorption/desorption of reaction intermediates, ultimately imparting excellent OER electrocatalytic activity.